2018
DOI: 10.5858/arpa.2017-0529-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Disruption of the Care Delivery System by Commercial Laboratory Testing in a Children's Health Care System

Abstract: Context.-Disruption of outpatient laboratory services by routing the samples to commercial reference laboratories may seem like a cost-saving measure by the payers, but results in hidden costs in quality and resources to support this paradigm.Objective.-To identify differences when outpatient tests are performed at the Children's Healthcare of Atlanta (Children's) Hospital lab compared to a commercial reference lab, and the financial costs to support the reference laboratory testing.Design.-Outpatient testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…To the Editor.-In their recent paper, Rogers et al 1 highlighted the increased costs that occur when a local laboratory testing system is disrupted and outpatient tests are sent to a commercial laboratory. We previously described how operational efficiencies should always be managed by clinical governance and should represent a tool for improving clinical effectiveness.…”
Section: Clinical Governance Should Be a Priority When Care Delivery mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor.-In their recent paper, Rogers et al 1 highlighted the increased costs that occur when a local laboratory testing system is disrupted and outpatient tests are sent to a commercial laboratory. We previously described how operational efficiencies should always be managed by clinical governance and should represent a tool for improving clinical effectiveness.…”
Section: Clinical Governance Should Be a Priority When Care Delivery mentioning
confidence: 99%
“…Although the difference was statistically significant (v 2 , P ,.001), we considered the overall performance of the offered service quite good. The analysis of time from the registration of outpatients and the check-in of their samples in the recipient laboratory for the same tests evaluated by Rogers et al, 1 that is, aspartate aminotransferase, C-reactive protein, erythrocyte sedimentation rate (ESR), low-density lipoprotein cholesterol, phosphate, and white blood cell count (WBC), showed that samples coming from IMH had a median delay of 50 minutes (interquartile range, 46-63 minutes) when compared with hub internal samples, compatible with the courier transportation schedule not affecting the samples arriving from the hub collection center. By considering the previously published 90th percentile turnaround times (TATs) of our hub structure, 3 we can conclude that in about 85% (42 100 of 49 534) of IMH outpatients, the time from phlebotomy to result posting in the EHR for WBC was less than 4.7 hours and for ESR was less than 5.3 hours, markedly better that the TATs reported by Rogers et al 1 Therefore, our organization based on principles of clinical governance 2,3 provides an effective health care system covering a large urban area in which the quality standards are overlapping and does not create a fragmented patchwork with different levels of service to end users.…”
Section: Clinical Governance Should Be a Priority When Care Delivery mentioning
confidence: 99%
“…These arguments are echoed in a 2008 report from the Centers for Disease Control and Prevention, stating that laboratory services are underrecognized as an essential component and partner in health systems. 8 Indeed, the potential negative impact on patient care and finances of divesting clinical laboratory assets has recently been reported from Children's Healthcare of Atlanta (Atlanta, Georgia), 9 and 2 joint ventures between a health system and a commercial lab were recently ended. 10 Currently, the short-term financial benefits from divestment and moneti-zation of their clinical laboratories may appeal to health system leadership 1 ; however, the wisdom of such divestment is being questioned, and alternative solutions for retaining control of this asset merit consideration.…”
mentioning
confidence: 99%
“…To the Editor.-We read with interest the article by Schifman et al 1 dealing with the utilization of measurement of free prostate-specific antigen (fPSA). We would like to contribute by reporting our experience about the management of fPSA requests by using a reflex testing approach and briefly discuss the status of the analytic control of this measurement.…”
mentioning
confidence: 99%
“…It was interesting to read that only about 16% of free PSA orders met guidelines, which was comparable to the proportion of cases (163 of 790, 20.6%), collectively that met similar testing criteria, among 28 Q-Probes participants. 1 Use of a reflex testing protocol in which total PSA is evaluated first as a prerequisite step to determine if free PSA is performed was a sound practice, which effectively eliminated most of the waste from unnecessary testing. Another potential benefit derived from reflex free PSA testing worth noting is prevention of diagnostic error by reducing risk that free PSA may be clinically misapplied if reported when total PSA is outside the interpretable range.…”
mentioning
confidence: 99%